Factors controlling sedimentation in the Toruń-Eberswalde ice-marginal valley during the Pomeranian phase of the Weichselian glaciation: an overview - Pisarska-Jamroży, Małgorzata (Geologos, 2015)
During the Pleistocene the Scandinavian ice sheet drained huge quantities of sediment-laden meltwaters. These meltwaters supplied ice-marginal valleys that formed parallel to the front of the ice sheet. Not without significance was the supply of ice-marginal valleys from extraglacial rivers in the south. Moreover, periglacial conditions during and after sedimentation in ice-marginal valleys, the morphology of valley bedrocks, and erosion of older sediments played important roles in the depositional scenarios, and in the mineralogical composition of the sediments. The mechanisms that controlled the supply and deposition in ice-marginal valleys were analysed on the basis of a Pleistocene ice-marginal valley that was supplied by northern and southern source areas in the immediate vicinity. Investigations were conducted in one of the largest ice-marginal valleys of the Polish-German lowlands, i.e., the Toruń-Eberswalde ice-marginal valley, in sandurs (Drawa and Gwda) supplied sediments and waters from the north into this valley, and on extraglacial river terraces (pre-Noteć and pre-Warta rivers), formed simultaneously with the sandurs and ice-marginal valley (Pomeranian phase of Weichselian glaciation) supplied sediments and waters from the south into this valley. A much debated question is how similar, or different, depositional processes and sediments were that contributed to the formation of the Toruń-Eberswalde ice-marginal valley, and whether or not it is possible to differentiate mostly rapidly aggraded sandur sediments from ice-marginal valley sediments. Another question addresses the contribution of extraglacial feeding of the Toruń-Eberswalde ice-marginal valley. These matters were addressed by a wide range of analyses: sediment texture and structure, architectural elements of sediments, frequency of sedimentary successions, heavy-mineral analysis (both transparent and opaque heavy minerals), analysis of rounding and frosting of quartz grains, and palaeohydrological calculations. Additionally, a statistical analysis was used. The specific depositional conditions of distribution of sediments in ice-marginal valley allow to distinguish new environment of ice-marginal valley braided river. The spectrum of depositional conditions in the Toruń-Eberswalde ice-marginal valley and their specific palaeohydraulic parameters allow to distinguish three coexisting zones in the ice-marginal valley braided-river system: (1) deep gravel-bed braided channel zone with extensive scours, (2) deep sand-bed braided channel zone with transverse bars, and (3) marginal sand-bed and gravel-bed braided channel zone with diamicton and breccia deposition, which were characterised in detail. Some of the results have been published previously, which is why they are discussed in the present paper within the context of new data